Analisa Beban Pada Rangka dan Poros Penggerak Mesin Pencuci Sampah Plastik Bekas dengan Software Solidworks 2016 - Fuja Fuji Hartono; Suherman Suherman (CV. IRA PUBLISHING, 2026)
The rising consumption of plastic poses significant environmental challenges due to its non-biodegradable nature. In the recycling process, the washing stage is critical for removing contaminants. This study aims to design and analyze a plastic waste-washing machine using SolidWorks 2016 Premium. The research methodology encompasses component design, mechanical parameter calculations, and static analysis simulations for the frame structure and stirrer shaft. The results indicate that the machine is powered by a 2 HP electric motor at 1400 rpm, with a pulley-and-V-belt transmission system. With dimensions of 1080 mm × 578 mm × 1000 mm, the machine achieves a washing capacity of 6 kg/hour. Simulation results demonstrate that the frame can withstand loads up to 3,810 N, which is significantly greater than the operational load of 560 N. Furthermore, the maximum stress on the stirrer shaft remains below the material's allowable limit, thereby satisfying structural safety criteria. These findings confirm that a simulation-based design approach can yield a structurally sound, operationally efficient washing machine, potentially enhancing the economic value of recycled plastics for small- to medium-scale recycling industries.